Evidence and proof in Scotland : context and critique - Nicolson, Donald (Edinburgh University Press, 2019)
This is the first textbook to set Scots evidence law against a modern backdrop of legal and empirical research. It examines the non-legal dimensions of evidence and proof through the lens of legal philosophy, procedure, sociology, science and psychology to analyse the contexts that affect the handling of facts and the process of proof.--